The failure to prevent World War I the unexpected armageddon - Gardner, Hall (Military strategy and operational art, 2014)
This book refines and expands points made in the author's earlier work on the failure to prevent World War I. It provides an alternative viewpoint to the thesis of Paul Kennedy, Fritz Fischer, among others, as to the war's long-term origins. By starting its analysis with the causes and consequences of the 1870-71 Franco-Prussian war, the study systematically explores the key geo-strategic, political-economic and socio-cultural-ideological disputes between France, Germany, Austria-Hungary, Russia, the United States and Great Britain, the nature of their foreign policy goals, alliance formations